Cześć!
[tex]\dfrac{x^{100}\cdot x^{43}\cdot x^{15}}{(x^5)^{24} \cdot (x^5)^2 \cdot x^{25}} =[/tex]
Zgodnie ze wzorem [tex](a^m)^n = a^{mn}[/tex]:
[tex]\dfrac{x^{100}\cdot x^{43}\cdot x^{15}}{x^{120} \cdot x^{10} \cdot x^{25}} =[/tex]
Zgodnie ze wzorem [tex]a^m \cdot a^n = a^{m+n}[/tex]:
[tex]= \dfrac{x^{100+43+15}}{x^{120+10+25}} = \dfrac{x^{158}}{x^{155}} =[/tex]
Zgodnie ze wzorem [tex]\frac{a^m}{a^n}=a^{m-n}[/tex]:
[tex]= x^{158-155} = x^3[/tex]
Dla [tex]x=-\frac{4}{3}[/tex], wartość wyrażenia to [tex](-\frac{4}{3})^3 = -\frac{4^3}{3^3} = -\frac{64}{27}[/tex]
Pozdrawiam!